IMPLEMENTASI AUTO VOLTAGE REGULATOR PADA SISI BEBAN ENERGI LISTRIK - Nur liya; Abdul Muis Prasetia (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Electrical energy is one of the basic needs in the present era, most human activities require electrical energy, so an increase in the need for electrical energy also increases, resulting in increased system problems. Voltage instability can also result in system problems and poor quality of electrical power. With a protection system, devices related to electricity will be safe and avoid damage. Auto Voltage Regulator is used to improve the voltage value at the point where the tool is installed. Auto Voltage Regulator (AVR) which is often used is a type of autotransformator. In this study, the PWM (Pulse Width modulation) dimmer is implemented as an AVR. Dimmer is an electronic circuit that modifies the form of a pure AC (Alternative Current) signal into a modulated signal so that the output voltage can be adjusted. The results of the test by providing a variety of different voltage input values. The system is obtained by providing an input value of 195 with a system output of 194, but if the system is given an input above the Set Point, the system is able to reduce the voltage up to 220 volts.